2001
DOI: 10.1046/j.0960-7692.2001.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal left ventricular transverse and long‐axis systolic function during pregnancy

Abstract: Changes in left ventricular long-axis performance during pregnancy occur earlier than do measures of transverse function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 49 publications
7
57
0
11
Order By: Relevance
“…In pregnancy, a previous cross-sectional study suggested that longitudinal function (assessed by M-mode) might deteriorate prior to circumferential function [assessed by EF and FS (fractional shortening)] [32]. With normal aging, a deterioration in longitudinal function, with preservation of circumferential function, has also been reported [43].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In pregnancy, a previous cross-sectional study suggested that longitudinal function (assessed by M-mode) might deteriorate prior to circumferential function [assessed by EF and FS (fractional shortening)] [32]. With normal aging, a deterioration in longitudinal function, with preservation of circumferential function, has also been reported [43].…”
Section: Discussionmentioning
confidence: 96%
“…Methodologically, although cross-sectional studies [31,32] have had an important role in highlighting the need for further research, determining normal values and establishing diagnostic utility in assessing maternal cardiac function during pregnancy will only be possible from longitudinal studies.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, there is conflicting information about left ventricular performance both during normotensive and hypertensive pregnancy. Normal, increased and depressed function have all been reported at various stages of gestation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 95%
“…Maternal cardiovascular adaptation to normal pregnancy includes increase in cardiac output 1,2 . Impaired placentation is associated with altered maternal cardiovascular function, which can lead to pre-eclampsia and/or intrauterine growth restriction (IUGR) 3,4 .…”
Section: Introductionmentioning
confidence: 99%